2022
DOI: 10.1073/pnas.2210536119
|View full text |Cite
|
Sign up to set email alerts
|

A proteome-wide map of chaperone-assisted protein refolding in a cytosol-like milieu

Abstract: The journey by which proteins navigate their energy landscapes to their native structures is complex, involving (and sometimes requiring) many cellular factors and processes operating in partnership with a given polypeptide chain’s intrinsic energy landscape. The cytosolic environment and its complement of chaperones play critical roles in granting many proteins safe passage to their native states; however, it is challenging to interrogate the folding process for large numbers of proteins in a complex backgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 92 publications
4
20
0
Order By: Relevance
“…For these categories, non‐contiguity is enriched 6.9‐fold, 5.6‐fold, and 5‐fold, respectively. The high propensity of non‐contiguity in these enzymes is consistent with their general inability to reversibly refold, 14,15 and is consistent with the conjecture that they co‐evolved with the emergence of protein synthesis by translation 32 …”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…For these categories, non‐contiguity is enriched 6.9‐fold, 5.6‐fold, and 5‐fold, respectively. The high propensity of non‐contiguity in these enzymes is consistent with their general inability to reversibly refold, 14,15 and is consistent with the conjecture that they co‐evolved with the emergence of protein synthesis by translation 32 …”
Section: Resultssupporting
confidence: 78%
“…We initially became intrigued with NC domains because recent studies found that E. coli proteins with NC domain topologies are generally less refoldable and rely more heavily on chaperones to assist their assembly. 14,15 These findings are consistent with the general understanding that long-range contacts in proteins are more challenging and slower to form. 16 With the recent upgrade to v2.0, 17 every protein record in Uniprot possesses a Family & Domains section which draws data from InterPro, 18 an EMBL-EBI database that compiles 13 protein signature databases including CATH-Gene3D, SCOP, and Pfam, among others.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…To experimentally test for the existence of these misfolded states, we unfolded purified 4-Diphosphocytidyl-2-C-Methyl-D-Erythritol Kinase (ispE) in 6 M guanidinium chloride, initiated refolding by dilution, and then probed the protein’s conformation with Limited Proteolysis Mass Spectrometry 18,19 (LiP-MS, see SI Methods). LiP-MS allows us to pinpoint subtle structural differences between folded and misfolded conformations 2,20 . Based on the predicted timescales from simulations, we allowed ispE three relatively long refolding times (1 h, 10 h, and 24 h, Table S8 and Supplementary Data) before probing it with limited proteolysis.…”
mentioning
confidence: 99%